(untitled) (Biological Sciences - PJSIR, 1998)
Equilibrium adsorption isotherms and rates of dyeing for Direct Red on cotton fibres pretreated with solutions of Valine, Threonine, Proline and Histidine in aqueous acetic acid were measured. Amino acid treatment increased the rate of dyeing with Direct Red and improved the wet fastness properties of the dyed cotton. At lower concentrations of amino acids, the order of exhaustion value was Threonine> Valine> Proline> Histidine whereas at higher concentrations, the order changed as Threonine> Proline> Valine> Histidine.